Effectiveness of feedback-based technology on physical and cognitive abilities in the elderly - Benitez-Lugo, Maria-Luisa; Suárez-Serrano, Carmen; Galvao-Carmona, Alejandro; Vazquez-Marrufo, Manuel; Chamorro-Moriana, Gema (Frontiers in Aging Neuroscience, 2022)
Aging raises a social and health challenge because the passing of time causes changes in cognitive and physical functions that impair functionality and quality of life. In addition, advancements in technology and information technology have led to the development of new techniques for retraining based on the feedback technology provides. To solve the negative consequences of aging, a randomized clinical trial was carried out to assess the effectiveness of a protocol using feedback-based technology to improve physical and cognitive functions in older adults. For the purpose of this study, 200 patients were selected from a Social and Community Services Center in the province of Seville and only 46 of them became participants of the study (after applying the inclusion criteria). These patients were divided into two groups: control and experimental. Physical and cognitive abilities were assessed using the Miniexamen cognoscitivo Test (an adaptation of the MiniMental examination test), Yesevage’s Depression Scale, Oddball Test, Attention Network Test, Berg Scale, Tinetti Scale, and Timed Up and Go Test. The intervention applied to the experimental group consisted of a supervised protocol using the Nintendo® Wii video game console and the Wii-Fit© video game during 16 sessions, 2 times a week with a duration of 30 min per session. The control group did not receive any treatment. The experimental group showed statistically significant improvements in all the physical variables (balance, gait, autonomy, and fall risk), as other authors had proven, and in memory and reaction times; there were no improvements in attention networks. The control group (placebo) even showed a decrease in their functions, with worse results on the Timed up and Go test Scale. The intervention using feedback-based technology has been proven effective in improving physical and cognitive abilities and in preventing and promoting healthy aging.